Acute myocardial infarction after embolism in a patient with paroxysmal atrial fibrillation - Gallegos Cazorla, Alex (2015)
Atrial fibrillation (AF) can produce embolism and remains as an important cause of morbidity and mortality. We report the case of a patient admitted with a history of palpitations and oppressive retro sternal pain. AF was found associated with ECG changes compatible with acute myocardial infarction. Biomarkers (Troponin T and CK-MB) and motility disorders assessed by echocardiography confirmed diagnosis and coronary angiography was performed. A total occlusion of posterior ventricular coronary artery branch was found, which was successfully treated with thrombus aspiration, reestablishing coronary flow. While AF can be commonly associated with acute myocardial infarction, thromboembolism secondary to AF producing total coronary occlusion is rare. This clinical scenario should be considered before stenting.